2011
DOI: 10.1002/cmdc.201100177
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐Free HIV‐1 Virucidal Action by Modified Peptide Triazole Inhibitors of Env gp120

Abstract: Virus interrupted! Initial entry of HIV‐1 into host cells remains a compelling and yet elusive target for developing agents to prevent infection. Here, we report the ability of modified, site‐ specific peptide triazole inhibitors that target HIV‐1 gp120 to physically disrupt virus particles in the absence of host cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
66
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 39 publications
(71 citation statements)
references
References 21 publications
3
66
1
1
Order By: Relevance
“…9 We further found that the terminal cysteine residue was required for luminal p24 release but was not essential for gp120 shedding, a phenotype displayed by non-sulfhydryl containing peptides ( 10 , HNG156, and 12 , UM15) and a sulfhydryl-blocked derivative ( 11 , KR13b). 8 Previously we synthesized a control peptide denoted KR13S, which contained a scrambled IXW pharmacophore (IWX).…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…9 We further found that the terminal cysteine residue was required for luminal p24 release but was not essential for gp120 shedding, a phenotype displayed by non-sulfhydryl containing peptides ( 10 , HNG156, and 12 , UM15) and a sulfhydryl-blocked derivative ( 11 , KR13b). 8 Previously we synthesized a control peptide denoted KR13S, which contained a scrambled IXW pharmacophore (IWX).…”
Section: Resultsmentioning
confidence: 80%
“…HIV-1 Env consists of 10 conserved disulfides, 9 of which are located within gp120 and the tenth in gp41. 9,1517 We speculate that, in order to reach specific gp120 disulfides, a minimum distance between IXW and the free SH group is required.…”
Section: Resultsmentioning
confidence: 99%
“…This class of compounds was found to induce shedding of gp120, thus inactivating the virus before cell encounter [9,10]. In addition, peptide triazole thiols (PTTs), PTs containing a free sulf-hydryl group (SH) on Cys at the C-terminus, were found to cause envelope disruption and p24 capsid protein release from the virus lumen [9,10]. The PTTs were initially made to conjugate to gold nanoparticles to form multivalent and consequently more potent inhibitors by providing the ability to interact with multiple Env proteins on single virions.…”
Section: Direct Virus Inactivation By Pts Discoveredmentioning
confidence: 99%
“…We previously identified a peptide triazole (PT) class of entry inhibitors that binds to HIV-1 Env gp120 with nanomolar affinity, inhibits cell infection by a broad range of virus subtypes and inactivates virus before host cell encounter by triggering gp120 shedding (Bastian et al, 2013; Bastian et al, 2011; McFadden et al, 2012). The ability of PTs to inhibit both CD4 and co-receptor binding sites in gp120, and the virus-inactivation functions of this class of inhibitors, appear to derive from entrapment of Env gp120 in a conformationally-disrupted and functionally-inactivated state.…”
mentioning
confidence: 99%
“…The ability of PTs to inhibit both CD4 and co-receptor binding sites in gp120, and the virus-inactivation functions of this class of inhibitors, appear to derive from entrapment of Env gp120 in a conformationally-disrupted and functionally-inactivated state. Importantly, we recently found that peptide triazole thiols and a multivalent form of the PT thiol KR13 displayed on gold nanoparticles (AuNP-KR13) were able to disrupt the virus particles, causing leakage of the internal protein p24 (Bastian et al, 2013; Bastian et al, 2011). The Env-inactivating functions of KR13 and AuNP-KR13 rely on the ability to disrupt the intrinsically metastable Env gp120/gp41 complex on the virus surface (Bastian et al, 2013; Bastian et al, 2015).…”
mentioning
confidence: 99%